ANALISIS KESALAHAN PESERTA DIDIK BERDASARKAN TAHAPAN KASTOLAN DALAM MENYELESAIKAN SOAL VEKTOR KELAS X SMA NEGERI 1 AMPEK ANGKEK - NURUL AUDHIFA UTAMI (Departemen Matematika, 2021)
Purpose of mathematics is one of the things that must be achieved when learning mathematics. To achieve this goal, students are expected to be able to master the direct objects of mathematics, so students understand the topic and do not make any mistakes. But based on the fact, students of X MIPA 4 SMA Negeri 1 Ampek Angkek still do the mistakes in solving mathematics problems and that means, students still not comprehend the topics and the purpose of mathematics still not reached. So, student error analysis is the solution to solve this problem. The research approach is qualitative and the type of research is descriptive. Subject of this research is X MIPA 4 SMA Negeri 1 Ampek Angkek with 9 students were interviewed. The data in this research are data from document analysis, test, and interview. Data analysis techniques in this research are reduction of data, data display, and conclusion. According to the research, there are 81,25% students do conceptual errors because they can’t select the formula well and still didn’t understand the topic, 14,06% students do procedural errors because they aren’t used to solve the variety of question, and 4,69% students do technical errors because of the their careless and time management.Keywords __ Student error analysis, kastolan, conceptual errors, procedural errors, technical errors, vector